The role of marketing in new ventures: How marketing activities should be organized in firms' infancy - Andreas Fürst; Mika Gabrielsson; Peter Gabrielsson; Jana-Kristin Prigge (Journal of the Academy of Marketing Science, 2023)
Although marketing activities are vital for new ventures (NVs) to ensure growth and survival, previous research is silent on how to organize them in firms' infancy. The entrepreneurship literature focuses on which marketing activities to perform in NVs but not on how to organize these activities, whereas the marketing literature concentrates on how to organize marketing activities in established firms but not in NVs, which face specific opportunities and challenges in their early stage of development. This article aims to tackle this research gap by examining marketing's role within NVs' organization. Drawing on in-depth interviews with managers, we identify two key organizational dimensions: marketing's dispersion (related to the proliferation and, thus, wide anchoring of marketing responsibilities) and marketing's structuration (related to the manifestation and, thus, deep anchoring of marketing responsibilities). Through a field survey and archival data, we show that marketing's dispersion enhances NV profitability, while marketing's structuration decreases it, and that with increasing marketing influence (i.e., power of marketing actors) in NVs and NV maturity (i.e., age and size), this diametrical pattern of effects becomes less pronounced. Overall, the findings provide novel theoretical and practical insights into the organizational design of marketing in firms' infancy.
Keywords: 330; Marketing's role; Marketing organization; Marketing function; Marketing department's influence; Marketing's power; Marketing responsibilities; Entrepreneurial marketing; Entrepreneurship